Decreased Cerebrospinal Fluid Flow Is Associated With Cognitive Deficit in Elderly Patients - Attier-Zmudka, Jadwiga; Sérot, Jean-Marie; Valluy, Jeremy; Saffarini, Mo; Macaret, Anne-Sophie; Diouf, Momar; Dao, Salif; Douadi, Youcef; Malinowski, Krzysztof Piotr; Balédent, Olivier (Frontiers in Aging Neuroscience, 2019)
Background Disruptions in cerebrospinal fluid (CSF) flow during aging could compromise protein clearance from the brain and contribute to the etiology of Alzheimer’s Disease (AD). Objective To determine whether CSF flow is associated with cognitive deficit in elderly patients (>70 years). Methods We studied 92 patients admitted to our geriatric unit for non-acute reasons using phase-contrast magnetic resonance imaging (PC-MRI) to calculate their ventricular and spinal CSF flow, and assessed their global cognitive status, memory, executive functions and praxis. Multivariable regressions with backward selection (criterion p<0.15) were performed to determine associations between cognitive tests and ventricular and spinal CSF flow, adjusting for depression, anxiety, and cardiovascular risk factors. Results The cohort comprised 71 women (77%) and 21 (33%) men, aged 84.1±5.2 years (range, 73¬–96). Net ventricular CSF flow was 52±40µL/cc (range, 0¬–210), and net spinal CSF flow was 500±295µL/cc (range, 0–1420). Ventricular CSF flow was associated with the number of BEC96 figures recognized (β=0.18, CI, 0.02–0.33; p=0.025). Spinal CSF flow was associated with the WAIS Digit Span Backward test (β=0.06, CI, 0.01–0.12; p=0.034), and categoric verbal fluency (β=0.53, CI, 0.07–0.98; p=0.024) and semantic verbal fluency (β=0.55, CI, 0.07–1.02; p=0.024). Conclusions Patients with lower CSF flow had significantly worse memory, visuo-constructive capacities, and verbal fluency. Alterations in CSF flow could contribute to some of the cognitive deficit observed in patients with AD. Diagnosis and treatment of CSF flow alterations in geriatric patients with neurocognitive disorders could contribute to the prevention of their cognitive decline.